2023
DOI: 10.1139/apnm-2022-0333
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in Canada: predictors of initiation, exclusivity, and continuation from the 2017–2018 Canadian Community Health Survey

Abstract: Human milk is the ideal source of nutrition for infants, however adherence to breastfeeding recommendations is suboptimal and availability of Canadian breastfeeding data is limited. Using the 2017-2018 Canadian Community Health Survey Public Use Microdata File (Maternal Experiences Module, n=5,558, weighted n=1,669,462) we computed breastfeeding indicators, and explored sociodemographic, health and geographical predictors of breastfeeding with univariate logistic regression models. Nationally, of all participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…91 % nationally) and exclusive feeding of human milk for 6 months at 30 % ( v . 35 % nationally) (21) .…”
Section: Methodsmentioning
confidence: 99%
“…91 % nationally) and exclusive feeding of human milk for 6 months at 30 % ( v . 35 % nationally) (21) .…”
Section: Methodsmentioning
confidence: 99%
“…To optimize infant and maternal health and infant development, global infant feeding recommendations include exclusive breastfeeding for the first six months of life ( 8 , 9 ). The most recent national Canadian data indicate that while 91% of infants initiated breastfeeding, only 35% exclusively breastfed to six months ( 10 ). As in other high-income countries, there are social disparities in breastfeeding as this behavior is negatively impacted by the social and structural determinants of health, including HFI ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In China and Europe, the rate is just 13%–39% and 29%, respectively 3 4. Many investigators have reported that PH is the most common cause of breastfeeding failure 5–7. Breast milk has been identified as the gold standard to provide nutritional support for all infants and prevent infant morbidity and mortality 8–10.…”
Section: Introductionmentioning
confidence: 99%
“…3 4 Many investigators have reported that PH is the most common cause of breastfeeding failure. [5][6][7] Breast milk has been identified as the gold standard to provide nutritional support for all infants and prevent infant morbidity and mortality. [8][9][10] For mothers, breast feeding can decrease the risk of breast cancer, ovarian cancer and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%